The Development of Pading Lake Tourism Destination Based on Community Empowerment on Former Mining Land in Perlang Village, Lubuk Besar District, Central Bangka Regency - Pratama, Imam Alfikri; Listari, Kiki (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This research aims to identify and map the social potentials of Sadap Hamlet, Perlang Village, in order to initiate tourist destinations that can affect the community empowerment process. The tourist destination cannot be separated from the utilization of former lead mining land known as 'kolong' into a water-based tourist attraction, namely Pading Lake. Initiated by the youth and the local community, Pading Lake has become a tourist destination that can provide income for the local community. This research focuses on the process of initiation and development of this tourist destination and explores the potentials of the Sadap Hamlet community and inhibiting factors for tourism development. This research used the concept of community empowerment and social capital. The perspective of community empowerment was used to see the empowerment process, while social capital was used to examine the potential or resources used in developing the tourist destination. This research used a qualitative method that emphasizes the deepening of meaning and phenomenon. The results of the analysis showed that community empowerment through the initiation and development of the Pading Lake used a bottom-up model or empowerment from the community itself (the community as the subject). The use of social capital such as networks, social media, and cooperation helps in the process of developing the Pading Lake tourist destination